Deteksi Tinggi Rendah Gelombang Air Laut Dengan Sistem Multi Sensor Berbasis Aplikasi Web Menggunakan Algoritma Naive Bayes - Jhosua Parningotan Sianipar; Randy Erfa Saputra; Casi Setianingsih (eProceedings of Engineering, 2021)
Indonesia is the largest archipelago in the world and has wider waters than land. Indonesia is also one of the countries most vulnerable to tsunami natural disasters. Tsunami is a natural disaster event in which sea waves with large size and high speed hit the coastal surface. Tsunamis usually occur due to tectonic earthquakes that occur on the seabed or the eruption of Mount Merapi located near the sea. Tsunamis don't just happen. This disaster has a process or anomaly in a ocean wave, such as the rapid receding of sea water. Currently the tsunami detection system already exists but this system is still very minimal in Indonesia because of the relatively high price. The purpose of this study is so that the public can monitor the current sea conditions. Created a web application with the help of the Laravel framework that can provide information on sea conditions in real time. This web application can also classify sea conditions in the form of